Transforming Chili Cultivation Through Environmentally Friendly Technology: Efforts to Achieve Sustainable Food Security in Indonesia - Didin Purniawan; Uci Musdalifah; Annisa .; Endah Nurmasita; Ayu Andira; Aisyah .; Wahyuni .; Magfirah .; Nurhafida .; Firdayanti .; Nurpadillah .; Bahtiar .; Dhea Oktaviani; Aminah . (Faculty of Engineering UNHAS, 2026)
This community service program was conducted in Lamunre Tengah Village, Belopa Utara District, Luwu Regency, to address the low productivity of chili (Capsicum annuum L.) caused by pest infestations, excessive reliance on chemical fertilizers, and farmers’ limited knowledge of eco-friendly agricultural technologies. The program aimed to enhance farmers’ knowledge, skills, and independence in sustainable agriculture practices through training on liquid organic fertilizer formulation, natural biopesticide production, and simple precision irrigation systems using soil moisture sensors. The methods included field observation, interactive counseling, hands-on demonstrations, and learning evaluation through pre-tests and post-tests administered to 15 participants. The results showed significant improvement across three main dimensions: understanding of eco-friendly technology increased from 33% to 47%, sustainable cultivation practices rose from 20% to 67%, and adoption of smart farming applications improved from 40% to 47%, with an overall average increase of 34%. In addition, participants demonstrated positive behavioral changes toward environmentally responsible innovation. These findings confirm that a participatory, learning-by-doing approach effectively strengthens farmers’ capacity and self-reliance while fostering the transformation of the local agricultural system toward efficiency, climate adaptability, and sustainability in support of national food security.